Quality of Life and Its Associated Factors among Inpatients with Pulmonary Tuberculosis - dwi prihatin era; Arifin Hidayat; Tini Tini; Abd Kadir (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2026)
Background: Tuberculosis affects patients' quality of life including physical, psychological, and social domains. Understanding demographic factors associated with quality of life is essential for comprehensive patient care. Objective: This study aimed to analyze demographic factors related to quality of life among hospitalized tuberculosis patients. Methods: A cross-sectional analytical survey was conducted at the Daisy Ward of RSUD Dr. H. Soemarno Sosroatmodjo, Tanjung Selor. Sixty-eight tuberculosis patients were selected using purposive sampling. Data were collected using demographic questionnaires and the WHOQoL-BREF instrument. Chi-Square test was used for bivariate analysis with significance level of 0.05. Results: Most respondents were elderly aged 46-60 years (67.6%), female (52.9%), highly educated (55.9%), employed (51.5%), and reported good quality of life (64.7%). Statistical analysis revealed significant correlations between quality of life and age (p=0.001), gender (p=0.032), education (p=0.046), and occupation (p=0.035). Elderly patients showed equal distribution between poor and good quality of life (33.8% each), while adult patients predominantly had good quality of life (29.4%). Female patients demonstrated better quality of life than males. Higher education and employment status were associated with better quality of life. Conclusion: All demographic factors including age, gender, education, and occupation significantly correlate with quality of life among hospitalized tuberculosis patients. Healthcare providers should consider these factors when developing holistic care strategies.